Crianças em área de vulnerabilidade social - Parra, Márcia Letícia de Vasconcelos (2011)
This study discusses the problematic of Brazilian children, from 7 to 13 years old that live and study in a socially vulnerable region, in an educative institution in a devoid community in Belo Horizonte/Minas Gerais. It points out some issues found in the children's lives and its effects in the process of formation of the learning desire. The cartographic method was used to raise the postures and the affections lived by this or that child in the territories they move. Among the theoretical referential authors, it can be highlighted Gilles Deleuze, Félix Guattari, Luiz B.L. Orlandi, Suely Ronilk and Sonia Regina Vargas Mansano. The study searched to decipher signs, to locate territories that made sense, to create other meanings for the sensations, making possible to the children to participate in a more powerful way of the cultural universe. Concomitant surveys have been carried through: schizo-analytical vectors favorable to cartography, especially the vector joy and the vector sadness, that had been associated to the children's life reality; survey of the concrete multiplicity, that is, of the hard lines that had composed the situation; survey of the statements that crossed certain situation in different sides; election of the children, in order to facilitate research; cartography of the postures that were distributed in longitude (movement and rest, speed and slowness) and latitude (ability to affect and to be affected) in the intensive and extensive meetings. Among the evaluated situations, notable points have been selected. They were organized and analyzed in four blocks: not-learning; drug traffic and violence; indiscipline, as a variation of the creative power and the control devices adopted by the school; and the situation of the imperfect bodies included in the school reality